IDENTIFIKASI KERAGAMAN JENIS BAKTERI PADA PROSES PENGOLAHAN LIMBAH CAIR INDUSTRI MINUMAN DENGAN LUMPUR AKTIF LIMBAH TAHU - Ritni Megasari; Danang Biyatmoko; Wahyuni Ilham; Jamzuri Hadie (EnviroScienteae, 2012)
The method of activated sludge is a wastewater treatment method that utilizes microbial growth processes are suspended.  One of the microbes that play a role in wastewater treatment systems with activated sludge are bacteria. The purpose of this research was to determine the effect of sampling time and the combination of retention time on levels of pH, BOD, TSS, H2S and turbidity effluent of beverage industry with waste activated sludge of tofu and identify the bacterial isolates obtained from the beverage industry wastewater treatment with activated sludge waste of tofu and to know the diversity of types of bacteria that play a role in it.  The diversity of bacteria identified in the beverage industry wastewater treatment by activated sludge are five types of Bacillus sp, Acinetobacter sp, Staphylococcos sp, Cardiobacterium sp, and Mycoplasma sp.  These bacteria are most likely a bacterium that plays a role in the degradation of the beverage industry wastewater. Activated sludge method, it is also able to improve water quality, especially for TSS parameter (<200 mg/l) and H2S (<0.05 mg/l).  Sampling time in the morning better than afternoon in the improvement of water quality parameters; for the retention time of 8 hours of sample treatment is better than 6 hours.  Thus, the retrieval time (morning, afternoon) and the retention time of wastewater samples generate all test parameters better than the control.